Nomogram for Quantitatively Estimating the Risk of Fibrosis Progression in Type 2 Diabetic Patients With Nonalcoholic Fatty Liver Disease: A Pilot Study - Xia, Jinying; Jin, Guang; Hua, Qifeng; Cui, Shihan; Li, Jianhui (Frontiers in Endocrinology, 2022)
Background Correct identification of the fibrosis progression risk is a critical step in the management of patients with type 2 diabetes mellitus (T2DM) and non-alcoholic fatty liver disease (NAFLD), because liver fibrosis, especially advanced liver fibrosis, is difficult to reverse. However, the progression of liver fibrosis is typically unnoticeable, leading to many patients failing to adhere to long-term therapeutic interventions. Reliable clinical tools for the quantification of the fibrosis progression risk may have effects on following long-term therapeutic recommendations to avoid further liver injury. Objective This study aims to develop a nomogram for quantitatively estimating the risk of fibrosis progression in T2DM patients with NAFLD during lifestyle intervention. Methods A total of 432 medical records of T2DM patients with NAFLD were retrospectively analyzed in this study. We divided patients into the progression and no-progression groups according to whether the value of liver stiffness measurement (LSM) increased by > 2 kPa at the last visit. The independent factors associated with the fibrosis progression, which were screened by univariate and multivariate Logistic regression, constituted the nomogram to determine the likelihood of fibrosis progression in T2DM patients with NAFLD. Results Sixty-five of the 432 individuals (15%) were found to have fibrosis progression. Changes in body mass index [odds ratio (OR) = 1.586], glycosylated hemoglobin A1c (OR = 6.636), alanine aminotransferase (OR = 1.052), and platelet counts (OR = 0.908) were independently associated with fibrosis progression (all P < 0.05) and functioned as components of the newly developed nomogram. It showed satisfied discrimination and calibration after 1,000 bootstrapping. The DCA indicated that the nomogram yielded clinical net benefit when the threshold probability was < 0.8. Conclusion We developed a nomogram incorporating dynamic alterations in clinical features to estimate the risk of fibrosis progression in T2DM patients with NAFLD, which aids the patients’ compliance with long-term life interventions while allowing for prompt intervention adjustments.